FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SEDIAAN SABUN CAIR EKSTRAK SABUT KELAPA (Cocos nucifera L. ) DENGAN VARIASI KONSENTRASI CARBOPOL 940 TERHADAP BAKTERI Staphylococcus aureus ATCC 25923 - Febriana Mukti Permata Sari; Siti Aisiyah; Destik Wulandari (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2023)
Shower gel is one of the preparations that can be used to protect the skin from Staphylococcus aureus bacterial infection. Plants that have antibacterial activity are coconut husk, the compounds contained are tannins, flavonoids, and polyphenols. Tannins have the activity of inhibiting the growth of Staphylococcus aureus bacteria. This study aims to determine the influence of Carbopol 940 variations on liquid soap preparations. Liquid soap preparations have antibacterial activity, find out which formulas have the best physical quality. Coconut husk extract was obtained by maceration method using 70% ethanol solvent. The concentration of coconut husk extract in the formula is 1.6% with a variation in the concentration of Carbopol 940 which is 0.5%, 1%, 1.5%. Physical quality examination includes organoleptic test, homogeneity test, pH test, viscosity, foam stability test, and free alkali test. Testing the antibacterial activity of liquid soap preparations using the method of diffusion of wells, the data obtained by analysis using the SPSS program. Variations in carbopol concentration 940 affect the physical quality of liquid soap preparations, the increasing concentration of carbopol affects viscosity, foam stability, and free alkali. All formulas have antibacterial activity of 21.23 (F4); 20.22 (F5); 19.37 (F6). The formula with the best physical quality and inhibitory power is formula 4 with a carbopol concentration of 940 of 0.5%.